Literature in an Open-Air Museum. Settlers from the Former Netherlands (Olenders) in Contemporary Cultural Heritage Discourse - Zduniak-Wiktorowicz, Małgorzata (Porównania, 2025)
The article presents the cultural heritage related to the centuries-old presence of settlers called Olenders – peasants from Flanders and Friesland, or pacifist Mennonites, who, in the 16th century, began to settle in the territories of what then was the Polish-Lithuanian Commonwealth. An analysis of contemporary practices of Olender heritage not only provides a glimpse into the recent changes in the understanding of cultural heritage itself, but also identifies opportunities for transdisciplinary research combining ethnography, museology and literary studies. Accordingly, the article also proposes an analysis of the literature on Olenders/Mennonites as an open-air museum narrative.